Tracing the local impacts of exports on poverty and inequality: The case of Mexico - Carlos Rodríguez-Castelán; Emmanuel Vazquez; Hernan Winkler (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2020)
Evidence about the effect of exports on welfare at the local level is scarce. Using a unique dataset of international trade and poverty maps for almost 2,000 Mexican municipalities between 2004 and 2014, the study presented in this paper provides new evidence on the impact of a significant rise in exports on poverty and inequality at the local level. The analysis implements an instrumental variable approach that combines the initial structure of exports across municipalities with global trends in exports from developing to developed countries by sector. The results show that a 10 percent increase in the ratio of exports to workers reduces income inequality measured by the Gini coefficient by 0.17 points (using a 0 to 100 scale), but no significant effects on poverty reduction or average household incomes are identified. The lack of impacts on average incomes is driven by a rise in the supply of labor at the local level because municipalities with higher export growth experienced an increase in labor force participation and attracted more net migration, particularly of unskilled workers. Therefore, while total labor incomes grew in response to an increase in exports, average labor incomes per worker did not change. Declining remittances also blunted the effect of growing exports on household incomes.
Keywords: F14; F16; I3; D3; J61; 330; International trade; exports; poverty; local impacts; migration